Relationships Between D-Dimer Levels and Stroke Risk as Well as Adverse Clinical Outcomes After Acute Ischemic Stroke or Transient Ischemic Attack: A Systematic Review and Meta-Analysis - Yuan, Bing; Yang, Tong; Yan, Tao; Cheng, Wenke; Bu, Xiancong (Frontiers in Neurology, 2021)
Abnormally elevated D-dimer levels are an important indicator of disseminated intravascular clotting. Therefore, we hypothesized that high D-dimer levels are associated with the risk of stroke as well as the adverse clinical outcomes of the patients with post-stroke or TIA. A meta-analysis was conducted to systematically analyze the association between D-dimer and the risk of stroke and the clinical outcomes of patients with post-stroke or TIA, while a dose-response would be conducted if sufficient data is available. Two investigators searched three electronic databases including Pubmed, the Embase database and the Cochrane Library. All the pooled results were performed by RRs. Finally, 22 prospective cohort studies were included. High D-dimer levels were associated with a higher risk of total stroke (RR 1.4, 95%CI 1.20–1.63), hemorrhagic stroke (RR 1.25, 95%CI 0.69–2.25), Ischemic Stroke (RR 1.55, 95%CI 1.22–1.98), whereas these dose-dependent relationship was not found through dose-response analyses. Besides, high D-dimer levels at admission were correlated with a increased risk of all-cause mortality(RR1.77, 95%CI 1.26–2.49),5d-recurrence (RR2.28, 95%CI 1.32–3.95),poor functional outcomes(RR2.01, 95%CI 1.71–2.36) in patients with AIS or TIA. High D-dimer levels might be associated with total stroke and IS, independent of HS. However, dose-response analyses lacked evidence for a dose-dependent association of D-dimer levels with stroke risk. Besides, high D-dimer levels at admission might be correlated with the risk of adverse clinical outcomes including all-cause mortality, 5d-recurrence and 90d-poor functional outcomes in patients with AIS or TIA. More studies are needed to quantify the effect of D-dimer levels on stroke or TIA to verify and substantiate this conclusion in the future.